Performance Analysis of PID and SMC Control Algorithms on AUV under the Influence of Internal Solitary Wave in the Bali Deep Sea - Wahyuadnyana, Kadek Dwi; Indriawati, Katherin; Darwito, Purwadi Agus; Aufa, Ardyas Nur; Tnunay, Hilton (Journal of Robotics and Control (JRC), 2024)
Autonomous Underwater Vehicles (AUVs) play a crucial role in deep-sea exploration, but their stability is often compromised by Internal Solitary Waves (ISWs) and nonlinear disturbances in stratified waters. This study aims to evaluate the performance of two control algorithms, Proportional-Integral-Derivative (PID) and Sliding Mode Control (SMC), in mitigating ISW effects on AUV trajectory tracking. Simulations were conducted in Simulink (MATLAB), modeling AUV dynamics under ISW disturbances with intensities ranging from 0% to 100%. The results reveal that both PID and SMC algorithms experience significant performance degradation as ISW intensity increases, with Root Mean Square Error (RMSE) values rising exponentially between 50% and 75% disturbance levels. While SMC offers better resilience to nonlinear disturbances than PID, neither algorithm fully compensates for high ISW intensities. These findings highlight the limitations of conventional control strategies and underscore the need for more robust, adaptive algorithms for reliable deep-sea AUV operations. Future work will explore Nonlinear Model Predictive Control (NMPC) for improved stability in complex marine environments.